Establishing a large-scale Greenhouse Gas Removal sector in the United Kingdom by 2030: First mover dilemmas. (June 2022) - Workman, Mark; Platt, Devon; Reddivari, Uday; Valmarana, Bianca; Hall, Steve; Ganpatsingh, Rob
Abstract: In June 2019 the UK legislated a 2050 net-zero emissions target. This will require the realisation of a technical Greenhouse Gas Removal (GGR) sector potentially generating over 60 MtCO2 pa of negative emissions by 2050. In October 2021, the UK pledged that at least 5 MtCO2 of engineered negative emissions be deployed by 2030. At present less than 0.5 ktCO2 pa of engineered negative emissions are deployed. The 10, 000-fold scale-up to 2030 will require the co-ordinated engagement of first movers to establish and realise at least one GGR value chain. The 120, 000-fold scale up to 2050 will require the integration of multiple GGR value chains with existing infrastructure systems and substantive societal engagement to enhance positive social outcomes. This scaling is fundamental to the UK, and arguably international efforts, to address the worst impacts of climate change. A series of exploratory exercises have been undertaken to identify the financial and non-financial barriers to the establishment of a UK multi-MtCO2 pa scale GGR sector from a first mover perspective. This is the first synthesis of first mover drivers in the UK GGR sector. The key findings include: (1) The GGR sector represents a multi-billion pound opportunity in 2050; and (2) inspite of this opportunity - as the incentive, policy, regulatory and governance ecosystem presently stands - first movers face too much risk, uncertainty and a multiplicity of dilemmas to commit substantive investments in establishing the UK GGR multi-MtCO2 pa sector.